The complete idiot's guide to iPad & iPhone app development - Brant, Troy. (Indianapolis, Ind. : Alpha, 2010)
You have all kinds of ideas you'd like to turn into apps. But it turns out designing those cool little programs isn't nearly as simple as using them-- but it can be! Learn to master the apps development kit so that you can start building your app right away.
Getting started. Welcome to the party! ; Your first app in a flash ; Interface building ; Buttons, controllers, and code ; Objective-C and Cocoa Touch ; Memory management -- Building your user interface. Switches, sliders, and controls ; Text fields ; Pickers ; Web views, spinners, and alerts -- Multi-view applications. View controllers ; Navigation controllers ; Tab bar controllers ; Table views ; Split views and popovers -- The APIs you can't wait to use. Animation ; Video, images, and audio ; GPS and location management ; iAd and multitasking -- Make your millions. Debugging in detail ; Testing apps on your device ; Tools of the trade ; The App Store and beyond.
Includes index and bibliographical references (p. 416-418).
Keywords: iPad (Computer) -- Programming; iPhone (Smartphone) -- Programming; Application software -- Development; iPad (Computer) -- Computer software; iPhone (Smartphone) -- Computer software; Application software -- Design